RISK DAN RETURN SAHAM PERUSAHAAN TELEKOMUNIKASI TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2021 - Karwati, Novianti Mufidah; Anindyntha, Firdha Aksari (Program Studi Ekonomi Pembangunan, 2023)
The purpose of this study determine the effect of market risk, debt to equity ratio, and earnings per share on stock returns in Telecommunications Sub Sector companies listed on the Indonesia Stock Exchange for 2017-2021 period. The objects in this study are all Telecommunications Sub Sector companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. This study used a purposive sampling technique in determining the research sample. There are 11 companies were obtained as research samples according to sample criteria. The analytical method used is panel regression. Based on the best model selection test, the model in this study is the random effect model. The results of the study show that market risk has a positive and significant effect on stock returns. While the debt to equity ratio and earnings per share have a significant negative effect on stock returns.